Flat, Cα, β‐Didehydroalanine Foldamers with Ferrocene Pendants: Assessing the Role of α‐Peptide Dipolar Moments. Issue 5 (6th April 2021) - Santi, Saverio; Bisello, Annalisa; Cardena, Roberta; Tomelleri, Silvia; Schiesari, Renato; Biondi, Barbara; Crisma, Marco; Formaggio, Fernando
Abstract: The foldamer field is continuously expanding as it allows to produce molecules endowed with 3D‐structures and functions never observed in nature. We synthesized flat foldamers based on the natural, but non‐coded, C α, β ‐didehydroalanine α‐amino acid, and covalently linked to them two ferrocene (Fc) moieties, as redox probes. These conjugates retain the flat and extended conformation of the 2.05 ‐helix, both in solution and in the crystal state (X‐ray diffraction). Cyclic voltammetry measurements agree with the adoption of the 2.05 ‐helix, characterized by a negligible dipole moment. Thus, elongated α‐peptide stretches of this type are insulators rather than charge conductors, the latter being constituted by peptide α‐helices. Also, our homo‐tetrapeptide has a N‐to‐C length of about 18.2 Å, almost double than that (9.7 Å) of an α‐helical α‐tetrapeptide. Abstract : Building bridges : Flat foldamers, adopting the peptide 2.05 ‐helix, were covalently bound to two ferrocene moieties, as redox probes. These conjugates preserve the flat and extended conformation both in solution and in the crystal state (X‐ray diffraction of single crystals). Cyclic voltammetry measurements are in agreement with the adoption of the 2.05 ‐helix, characterized by a negligible dipole moment. Thus, this type of elongated, α‐peptide foldamer is acting as insulators rather than a charge conductor.